Pushing, Pulling, Twisting, Stretching: the Power of Light under the Microscope - Philip Jones (Opticon1826, 2009)
Of the many uses we have for light such as illumination or digital communication, perhaps the most surprising is physical manipulation of matter. Holding and moving objects without touching them may seem like the stuff of science fiction, but a profound understanding of the interaction between light and matter can make this a reality, at least on the microscopic scale. Since its invention, the technique of ‘optical trapping’ has evolved into a tool with applications beyond the narrow scope of physics, and in particular, has enabled remarkable discoveries in biology and medicine.
Keywords: optical trapping; optical tweezers; optics